A self-healing liquid metal anode with PEO-Based polymer electrolytes for rechargeable lithium batteries. (December 2020) - Li, Tianyi; Cui, Yi; Fan, Longlong; Zhou, Xinwei; Ren, Yang; De Andrade, Vincent; De Carlo, Francesco; Zhu, Likun
Highlights: A Ga-Sn liquid metal nanoparticle electrode was fabricated via super ultrasonication and surfactant additives. The chemical and crystalline evolutions of Ga-Sn liquid metal anodes were investigated via synchrotron transmission X-ray microscopy and X-ray diffraction. The Ga-Sn liquid metal anode demonstrates a better capability to maintain its mechanical integrity and better contact with PEO solid electrolytes due to its advantageous features of the liquid. Abstract: Ga-Sn liquid metal material is demonstrated as a self-healing anode system due to its fluidity via operando synchrotron-based transmission X-ray microscopy and X-ray diffraction experiments. Cracks formed due to volume expansions can be recovered by the fluidity of the liquid metals. By incorporating with a poly(ethylene oxide) (PEO)-based electrolyte at 60 °C, the Ga-Sn anode shows a reversible lithium insertion and extraction process with a high initial discharge specific capacity of 682 mAh g − 1, followed by delivering a capacity of 462 mAh g − 1 in the second cycle at C/20 rate. Compared with its solid counterparts, the Ga-Sn liquid metal anode demonstrates a better capability to maintain its mechanical integrity and better contact with PEO solid electrolytes due to its advantageous features of the liquid. This study suggests a potential strategy to use liquid metal alloys with polymer solid electrolyte to solve the challenges in rechargeable lithium batteries. Graphical abstract: Image, graphical abstract